Fabrication and mechanical properties of biomimetic nacre-like ceramic/polymer composites for chairside CAD/CAM dental restorations. Issue 1 (January 2022) - Algharaibeh, Sana; Wan, Hongbo; Al-Fodeh, Rami; Ireland, Anthony J.; Zhang, Dongsheng; Su, Bo
Abstract: Objective: To fabricate and characterise a novel chairside CAD/CAM composite dental materials. These composites have a nacre-like anisotropic microstructure, consisting of highly aligned ceramic scaffolds infiltrated with polymer. Method: Bi-directional freeze casting of alumina ceramic suspension was used to fabricate highly aligned ceramic scaffolds that were subsequently uniaxially pressed to control the ceramic volume fraction and then infiltrated with UDMA/TEGDMA polymer. The produced composites were subjected to mechanical testing, namely three-point bending, hardness and fracture toughness tests. Results: Novel biomimetic ceramic/polymer composites (BCPCs) were fabricated with nacre-like brick and mortar anisotropic microstructure. The mechanical properties were dependent on the ceramic volume fraction. The 70 vol% BCPC had sufficient flexural strength (135.08–145.77 MPa), stiffness (57.75–61.22 GPa) and hardness (3.07–3.36 GPa) and showed remarkable fracture resistance with KIC value of (2.54 MPa m 1/2 ). Significant: Novel biomimetic ceramic/polymer composites show great potential as the next generation of CAD/CAM dental materials, as they closely resemble the combined mechanical properties of dentine and enamel.